The Nehrus Motilal and Jawaharlal - Nanda, B. R. (Bal Ram), 1917-2010. (New Delhi ; Oxford : Oxford University Press, 2008)
Motilal and Jawaharlal Nehru were both prominent Indian men in their own right, Motilal as a widely successful civil lawyer and a popular political figure, and Jawaharlal as a firm nationalist leader and possible heir of the Mahatma. This book discusses Motilal's life and achievements, and examines the first four decades of Jawaharlal's life. It shows that while the father-son tandem played different roles in the nationalist struggle of India, their close emotional bonds helped them influence each other.
This ed. originally published: London : George Allen & Unwin, 1962.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Nehru, Motilal, -- 1861-1931.; Nehru, Jawaharlal, -- 1889-1964.; Statesmen -- India -- Biography; Prime ministers -- India -- Biography; India -- Politics and government -- 1765-1947.